Home care for advanced cancer: Results and challenges - Pannuti Franco (Archive of Oncology, 2010)
The majority of palliative care patients prefer home care and 70% of terminal cancer patients want to die at home. Only a well-organized network of specialized oncology, home care and hospices/palliative care units can guarantee the fundamental human right of advanced cancer patients to live and die with dignity, what we call Eubiosia. We consider the Bologna Eubiosia Project initiated by ANT in 1985 and supported by numerous political, religious and private bodies independent from their political color, as an example of successful fighting against human suffering. However, there is no doubt that Eubiosia has to be realized at the beginning of the 21st century in a way, different from the one of 30 years ago. Globalization and demographic changes create needs for new approaches. Telecare is a reasonable approach to overcome existing problems. ANT has started the first steps to preserve our moral values in a rapidly developing world by using new highly sophisticated health technologies. We believe that Techno-Eubiosia is a new challenge for caregivers and for the producers of medical devices in the 21st century.